Production of pions, kaons, and (anti-)protons in Au+Au collisions at √SNN = 54.4 GeV at RHIC - Gopal Krishan (EPJ Web of Conferences, 2023)
We report systematic measurements of bulk properties of the system created in Au+Au collisions at √SNN = 54.4sNN=54.4 GeV recorded by the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The transverse momentum spectra of π±, K±, and p(p¯)p(p¯) are studied at mid-rapidity (|y| < 0.1) for different centrality classes. We also present mid-rapidity measurement of particle yields (dN/dy) and particle ratios in Au+Au collisions at √SNN = 54.4sNN=54.4 GeV. The kinetic freeze-out parameters (Tkin and β>) are extracted from particle spectra using the blast-wave model, and all the results are compared with previously published experimental results.